Mothers' nonstandard work schedules and adolescent obesity: a population-based cross-sectional study in the Tokyo metropolitan area - Yuko Kachi; Aya Abe; Hisashi Eguchi; Akiomi Inoue; Akizumi Tsutsumi (BMC, 2021)
Abstract Background Many wage earners in developed countries have irregular shift patterns and work evenings, nights, and weekends. Some studies have demonstrated that the nonstandard work schedules of parents have adverse effects on their children's weight, specifically leading to or worsening obesity. However, no such study has been conducted in adolescents of high school age. This study examined the association between mothers' nonstandard work schedules and adolescent obesity. Methods A cross-sectional study of adolescents aged 16-17 years (n = 1743) used paired matches of self-administered questionnaires for adolescents and their mothers from Tokyo, Japan. Obesity was defined by International Obesity Task Force cut-offs. Nonstandard work schedules were defined as working early mornings, nights, overnights, or weekends. Chi-square tests were conducted to examine the association between the mothers' work schedules and their adolescent children's poor lifestyles, overall and stratified by income levels. Then, logistic regression analyses were conducted to examine the association between mothers' work schedules and obesity of their adolescent children, overall and stratified by income levels. Results Overall, 6.5% of adolescents had obesity. The prevalence of obesity was higher among adolescents from low-middle income groups (8.2%) than that among those from high-income groups (5.9%). No clear patterns were found between mothers' work schedules and adolescents' poor lifestyles when stratified by income levels. Mothers' nonstandard work schedules were significantly associated with adolescent obesity (odds ratio [OR]: 1.56, 95% confidence interval [CI]: 1.02-2.40). However, this association was not significant after adjustment for confounders. After stratification by income levels, mothers' nonstandard work schedules significantly associated with their children's obesity (OR: 2.93, 95% CI: 1.45-5.92) only in high-income groups. This association remained after adjustment of the adolescents' lifestyles and their mothers' working hours. Conclusions Our results suggest that mothers' nonstandard work schedules have adverse effects on adolescent obesity only in high-income families. Low-middle income families experienced higher levels of adolescent obesity, regardless of the mothers' work schedules. Policy makers should consider mothers' work schedules as a factor in preventing adolescent obesity.